Models to predict mortality of Tribolium castaneum (Coleoptera: Tenebrionidae) exposed to elevated temperatures during structural heat treatments - Jian, Fuji; Subramanyam, Bhadriraju; Jayas, Digvir S.; White, Noel D. G. (My University, 2014)
Novel thermal death models were developed with certain assumptions, and these models were validated by using actual heat treatment data collected under laboratory conditions at constant temperatures over time and in commercial food-processing facilities where temperatures were dynamically changing over time. The predicted mortalities of both young larvae and adults of the red flour beetle, Tribolium castaneum (Herbst), were within 92–99% of actual measured insect mortalities. There was good concordance between predicted and observed mortalities of young larvae and adults of T. castaneum exposed to constant temperatures in laboratory growth chambers and at variable temperatures during structural heat treatments of commercial food-processing facilities. The models developed in this study can be used to determine effectiveness of structural heat treatments in killing young larvae and adults of T. castaneum and for characterizing insect thermotolerance.
Keywords: Tribolium castaneum; Mortality; Heat treatment; Food-processing facility; Model